2017
DOI: 10.1017/s1368980017002804
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dietary vitamin D and serum 25-hydroxyvitamin D levels in Portuguese adolescents

Abstract: Dietary vitamin D and serum 25(OH)D levels were positively but weakly correlated and the error was higher among those with higher serum 25(OH)D concentration. Our results support the need for strategies that promote increase of the most important food sources of vitamin D to reduce the high prevalence of low vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Adequacy of food intake during pregnancy determines the adequacy of maternal nutrition, and in terms of vitamin D intake, foods rich in this nutrient are not as common as other vitamin sources. Recent studies showed that low vitamin D food intake during pregnancy was positively but weakly correlated with maternal serum vitamin D level (25-hydroxyvitamin D) [4]. Our previous studies had no association between vitamin D and calcium food intake status.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Adequacy of food intake during pregnancy determines the adequacy of maternal nutrition, and in terms of vitamin D intake, foods rich in this nutrient are not as common as other vitamin sources. Recent studies showed that low vitamin D food intake during pregnancy was positively but weakly correlated with maternal serum vitamin D level (25-hydroxyvitamin D) [4]. Our previous studies had no association between vitamin D and calcium food intake status.…”
Section: Introductionmentioning
confidence: 57%
“…It is easier for pregnant women who live in coastal areas to access vitamin D-rich foods in seafood such as fatty fish (mackerel, tuna, salmon and sardines), fish oil, oysters, prawns and cod liver oil than for those who live in mountainous areas. A recent study showed that 37% of vitamin D food intake source was coming from seafood, followed by starchy, meat, eggs, dairy, and sweet and pastry foods [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the EpiFloripa study, for instance, a correlation of 0.06 was observed between intake (assessed in 2012) and serum levels of vitamin D (collected in 2014) (data not shown). Given the weak, if any, correlation between vitamin D intake and serum levels [25(OH)D] ( 36 ), it is possible to speculate that the null association between vitamin D and periodontitis might have resulted from the lack of data on 25(OH)D. Another potential explanation for this null association might relate to the age of our sample, as an inverse association between vitamin D and periodontitis was observed only among Americans over 50 years ( 37 ). Therefore, future studies with a broader age sample are encouraged to clarify this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2021 also fortified milk is available [ 60 ] The Netherlands No mandatory fortification; voluntary fortification previously allowed only for certain fats and oils, no more than 0.075 µg/g[ 61 ], now apparently also some cereals, dairy products and drinks are fortified with 30–650 IU/100 g [ 62 ] [ 61 , 62 ] Poland No fortification (except milk formulas for infants and toddlers) [ 63 ] Portugal No fortification policy/no mandatory fortification, but some fortified foods such as yoghurts, milk, breakfast cereals, etc. are available in the market [ 64 , 65 ] Spain Fortification is voluntary for all foods except for infant formulas and infant cereals. Moreover, (…) there is a tendency to fortify skimmed and semi‐skimmed milks with vitamin D to reach the initial levels of whole milk; in addition, some commercial products are fortified with vitamin D such as biscuits, yoghurt, margarine, cheese, cereals and juices [ 66 ] Romania “In Romania dietary sources of vitamin D are scarce and there is no fortification of food with vitamin D.” [ 67 ] Slovakia No special legislation concerning fortification (vitamin D may be voluntary added to foods) (corr.…”
Section: Introductionmentioning
confidence: 99%